مسلم ریاست میں غیر مسلم شہریوں کا تحفظ(جدید بین الاقوامی تصور اور عہد نبویؐ و عہد خلفائے راشدین کا تعامل) - ڈاکٹر اکرام الحق یٰسین (FIKR-O NAZAR فکر ونظر, 2011)
Rights of minorities is a burning issue today among the debates on human rights. This article tries to explore the most appropriate form of the rights of the non muslim citizens of a muslim state wide a comperative discussion between the existing international law and the practices of the prophetic era and during the time of the rightly guided caliphs. The discussion undertakes the use of the word "monorities" and shows that it is not a respectful word for the citizens of a country. It has never been used in the Islamic history, rather the words of "one nation" as in the Madinah treaty and other respectful words like "Ahl alDhimmah (people of responsibility)" and "Ahl al- kitab (followers of the book)" have been used for non muslim citizens. Kinds of monorities have also been discussed and it is concluded that dividing the members of one nation into the minorities on ethnic, cultural and langual basis has no link with the human rights, rather it causes the tention and creates conflict between the members of a nation. The holy Prophet Muhammad (S.A.W,) scrupulously negated all kind of pride or preference on the basis of race, language and colour as it is clear from his sermon on the occasion of Hijjatul wada'. A comparison between the international charters and Islamic traditions has been made and it is concluded that Islam has from its very begining ensured the protection of human rights and given the non muslim citizens a respectful status and complete religious freedom.